Penerapan Model Pembelajaran Eksperiental Jelajah Alam Sekitar (EJAS) untuk Meningkatkan Kecerdasan Naturalis dan Hasil Belajar Kognitif IPA Siswa SMP - Sanni Indri Astuti; Rina Rahayu; Eli Trisnowati (INKUIRI: Jurnal Pendidikan IPA, 2026)
Penelitian ini memiliki tujuan yang mencakup : (1) Menganalisis keefektifan model pembelajaran EJAS dalam meningkatkan kecerdasan naturalis siswa; (2) Menganalisis keefektifan model pembelajaran EJAS dalam meningkatkan hasil belajar kognitif IPA siswa SMP; (3) Menganalisis hubungan kecerdasan naturalis siswa dengan hasil belajar kognitif IPA siswa SMP pada penerapan model pembelajaran EJAS. Penelitian ini memakai desain Quasi Eksperimental Design dalam bentuk pretest-posttest nonequivalent control group design. Populasi penelitian ini yakni siswa kelas VII SMP Negeri 2 Muntilan Tahun Ajaran 2023/2024 sejumlah 2 kelas dengan teknik pengambilan sampel berupa purposive sampling. Hasil penelitian menunjukkan; (1) Penerapan model pembelajaran EJAS efektif dalam meningkatkan kecerdasan naturalis siswa; (2) Penerapan model pembelajaran EJAS efektif dalam meningkatkan hasil belajar kognitif IPA siswa SMP; (3) Terdapat hubungan positif antara kecerdasan naturalis dengan hasil belajar kognitif dengan besar pengaruh kecerdasan naturalis terhadap hasil belajar kognitif sebesar 16,3%.This research has objectives that include: (1) Analyzing the effectiveness of the EJAS learning model in increasing students' naturalistic intelligence; (2) Analyze the effectiveness of the EJAS learning model in improving junior high school students' science cognitive learning outcomes; (3) Analyzing the relationship between students' naturalistic intelligence and junior high school students' science cognitive learning outcomes when implementing the EJAS learning model. This research uses a Quasi Experimental Design in the form of a pretest-posttest nonequivalent control group design. The population of this research is class VII students of SMP Negeri 2 Muntilan for the 2023/2024 academic year in 2 classes with a sampling technique in the form of purposive sampling. The research results show; (1) The application of the EJAS learning model is effective in increasing students' naturalistic intelligence; (2) The application of the EJAS learning model is effective in improving junior high school students' science cognitive learning outcomes; (3) There is a positive relationship between naturalist intelligence and cognitive learning outcomes with a large influence of naturalist intelligence on cognitive learning outcomes of 16.3%.